1995
DOI: 10.1128/mcb.15.7.3882
|View full text |Cite
|
Sign up to set email alerts
|

RNA Template Requirements for Target DNA-Primed Reverse Transcription by the R2 Retrotransposable Element

Abstract: R2 is a non-long terminal repeat-retrotransposable element that inserts specifically in the 28S rRNA gene of most insects. The single protein encoded by R2 has been shown to contain both site-specific endonuclease and reverse transcriptase activities. Integration of the element involves cleavage of one strand of the 28S target DNA and the utilization of the exposed 3 hydroxyl group to prime the reverse transcription of the R2 RNA transcript. We have characterized the RNA requirement of this target DNA-primed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
189
1
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(197 citation statements)
references
References 40 publications
6
189
1
1
Order By: Relevance
“…L1 RT template jumping during a twin priming reaction likely explains the addition of 7 nt in another integrant (Supplemental Discussion 3). While to the best of our knowledge, RT template jumping during twin priming has not been reported previously, our results are consistent with the conceptually similar TPRT initiation, which occasionally creates 3Ј extra nucleotides due to the repeated attempts of RT to fully engage the RNA template (Luan and Eickbush 1995;Eickbush et al 2000;. The longer 47 extra-nucleotide addition was likely created by a series of three successive template jumps by L1 RT in the course of an otherwise unremarkable TPRT reaction (Fig.…”
Section: Extra Nucleotide Formation At 5ј Ends Of L1 Integrantssupporting
confidence: 78%
See 1 more Smart Citation
“…L1 RT template jumping during a twin priming reaction likely explains the addition of 7 nt in another integrant (Supplemental Discussion 3). While to the best of our knowledge, RT template jumping during twin priming has not been reported previously, our results are consistent with the conceptually similar TPRT initiation, which occasionally creates 3Ј extra nucleotides due to the repeated attempts of RT to fully engage the RNA template (Luan and Eickbush 1995;Eickbush et al 2000;. The longer 47 extra-nucleotide addition was likely created by a series of three successive template jumps by L1 RT in the course of an otherwise unremarkable TPRT reaction (Fig.…”
Section: Extra Nucleotide Formation At 5ј Ends Of L1 Integrantssupporting
confidence: 78%
“…While decapping of most cellular mRNAs requires prior shortening of the poly(A) tail (for review, see Coller and Parker 2004), we and others observed no difference between poly(A) lengths of 5Ј-truncated and FL integrants. This may imply that shortened L1 poly(A) tails are extended by the RT during TPRT initiation (Luan and Eickbush 1995;Eickbush et al 2000;Cost et al 2002) or are subject to additional polyadenylation after re-entry of L1 RNA into the nucleus.…”
Section: Model Of 5ј-end Attachment and L1 Integrationmentioning
confidence: 99%
“…Target-primed reverse transcription and second-strand synthesis reconstruct the retrotransposon DNA for insertion at the new locus. 123,124 Until recently, the factor responsible for the cotranscriptional processing of the element was unknown, even though the processing was discovered over 25 years ago. 125 Recently, it has been confirmed that this event is due to the action of a self-cleaving ribozyme of an HDV-like motif (Fig.…”
Section: R2 Ribozymesmentioning
confidence: 99%
“…The latter would allow synthesis of both the complementary DNA and second strand DNA necessary to complete the element's integration starting from RNA. It is capable of adding nontemplate nucleotides (usually T residues), has high processivity (Luan and Eickbush, 1995), and low fidelity (Jamburuthugoda and Eickbush, 2011).Our preliminary work showed that the ORF2 protein encoded by EhLINE1 (recombinant fulllength ORF2p) has RT activity with various substrates, including poly (rA)-oligo(dT), and a 120 nt RNA template from the 3'-end of EhSINE1. EhLINE1-ORF2p seems to have considerably high processivity in vitro as full length cDNA was the major product with very few lower-sized products.…”
mentioning
confidence: 99%
“…The latter would allow synthesis of both the complementary DNA and second strand DNA necessary to complete the element's integration starting from RNA. It is capable of adding nontemplate nucleotides (usually T residues), has high processivity (Luan and Eickbush, 1995), and low fidelity (Jamburuthugoda and Eickbush, 2011).…”
mentioning
confidence: 99%